Veil-Piercing: Corporate Criminal Liability, Governance and Reform in Indonesia and The UK - Irene Berlinda Fajarrani; Sri Astutik; Nur Handayati (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
This article examines the doctrine of piercing the corporate veil in criminal law through a comparative study of Indonesia and the United Kingdom. The study employs a doctrinal methodology, analyzing statutes, case law, and regulatory frameworks to evaluate how each jurisdiction balances corporate governance with legal accountability. The comparative analysis highlights key differences in legal enforcement and procedural thresholds, revealing the evolving nature of corporate criminal liability and corporate responsibility in both jurisdictions. Key findings suggest that recent legislative initiatives and judicial developments have strengthened mechanisms for holding corporate actors accountable, though significant variations in enforcement persist. The study proposes targeted corporate governance and legal reforms to improve accountability and deter misconduct, underscoring the value of comparative insights for policy Development. These findings offer practical recommendations to strengthen corporate governance and prevent wrongdoing in both jurisdictions. By bridging the gap between Indonesian and UK legal perspectives, this research serves as a strategic roadmap for policymakers seeking to refine legal sanctions and promote a culture of corporate integrity.